The Relationship between Environmental and Behavioral Factors and the Incidence of Diarrhea in Toddlers in the Work Area of the Waru Community Health Center, Sidoarjo Regency - Achmad Sholeh Farhat; Mochammad Bagus Qomaruddin (International Journal of Health and Pharmaceutical (IJHP), 2026)
Diarrhea is a public health problem that significantly contributes to morbidity, particularly in vulnerable age groups such as under-five children. Various efforts to treat diarrhea have been implemented through primary health care, but the incidence of diarrhea in under-five children remains quite high, including in the Waru Community Health Center in Sidoarjo, which experienced an increase in diarrhea cases in 2023-2025. The incidence of diarrhea in under-five children is influenced by various interrelated factors, particularly environmental and behavioral factors, which, according to Hendrik L. Blum's theory of health determinants, play a role in influencing health status. This study aims to analyze the relationship between environmental and behavioral factors and the incidence of diarrhea in under-five children in the Waru Community Health Center in Sidoarjo. This study was a quantitative, observational, and analytical study using a cross-sectional approach. It was conducted among 89 mothers of under-five children who visited the Waru Community Health Center in Sidoarjo from January to March 2026. Data were collected through interviews using questionnaires and direct observation of the environmental sanitation conditions of the respondents' homes. Data analysis was conducted using descriptive and inferential statistics with the chi-square test. The results showed that among environmental factors, the condition of healthy latrine could not be statistically tested (constant), while clean water sources (p = 0.080), household waste management (p = 1,000), and wastewater drainage systems/SPAL (p = 1,000) were analyzed. Meanwhile, behavioral factors included the use of healthy latrines (p = 0.018), handwashing with soap (p = 0.348), drinking water treatment (p = 0.478), and exclusive breastfeeding (p = 0.048). This study concluded that the use of healthy latrine and exclusive breastfeeding were factors associated with the incidence of diarrhea among under-five children in the Waru Community Health Center in Sidoarjo. The Community Health Center is recommended to conduct regular monitoring and mapping of at-risk areas as a basis for determining priority diarrhea prevention interventions.